Ibm USAHA BAKSO DI LINGKUNGAN GLADAK PAKEM JEMBER - Ningsih, Wiwik Fitria; Maspufah, Hayatul (Universitas Pendidikan Ganesha, 2018)
The goal to be achieved in this IbM program is to improve the economic capability of IbM partners by speeding up the process of improving human resources capability in the field of meatball sales of Mitra IbM. Approach method offered to solve partner problem that is by using method of PLA / Participatory Learning And Action. The PLA method is used in solving the problems of related partners in designing and running the production of meatball products to be sold, designing new media for its marketing system and also to supervise and evaluate the program of Ibm Usaha Bakso in Gladak Pakem Jember. The indicator of success of Ibm program are the increasing number of meatball products offered, bakso tripe and mushroom meatballs; The increasing of marketing media used is using banner with striking color to take the attention of consumer; And increased sales turnover.